ADMINISTRATIVE MANAGEMENT IN IMPROVING QUALITY OF ACADEMIC SERVICES - Nur Hidayat, Fitri (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Madrasah Ibtidaiyah (MI) At-Taqwa is one of the leading educational institutions in the city of Bondowoso. This institution has succeeded in gaining very good trust from the community, one proof is that the number of students who register each year exceeds the targeted number and its students at this institution always achieve both academic and non-academic achievements. Seeing this reality, it is impossible to be separated from good and directed administrative management at the madrasah. This study aims to describe administrative management at MI At-Taqwa Bondowoso which includes planning, organizing, implementing and supervising administration in improving the quality of academic services. This research approach is qualitative with a descriptive type. Data collection techniques using observation, interviews, and documentation which are then analyzed to obtain data or information. The subjects of this study include the head of the madrasah, the head of administration, and the administrative staff at MI At-Taqwa Bondowoso. For the validity of the data, the researcher used triangulation. The results of this study are that administrative management in improving the quality of academic services at MI At-Taqwa Bondowoso starts from formulating planning, then dividing tasks (job descriptions), then implementing the formulated plans in the form of several workprograms in each part of the administration, then monitoring and evaluation by the head of the madrasah regarding administrative performance at the MI At-Taqwa Bondowoso Institution.